2020
DOI: 10.1161/hypertensionaha.120.14777
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Statins, Cav1 (Caveolin-1), and Aldosterone

Abstract: Statin use is associated with lower aldosterone levels. We hypothesized that caveolin-1 may be important for the uptake of statins into the adrenal gland and would affect statin’s aldosterone-lowering effects. The aim of this study was to test whether the caveolin-1 risk allele (rs926198) would affect aldosterone levels associated with statin use. The Hypertensive Pathotype database includes healthy and hypertensive individuals who have undergone assessment of adrenal hormones. Individuals were studied off ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…It is also crucial for cholesterol transmembrane transport, accumulation and efflux; as it is the primary component of caveolae. In contrast with the current results, previous studies found that statin decreased the expression of CAV1 emphasizing a probable correlation between statins and CAV1 also suggesting a potential pleiotropic value of statins beside lipid reduction [ 64 ]. In contrast another study reported that statin increased CAV1 expression, but decreased the density of caveolae while the overall raft density was unaffected.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also crucial for cholesterol transmembrane transport, accumulation and efflux; as it is the primary component of caveolae. In contrast with the current results, previous studies found that statin decreased the expression of CAV1 emphasizing a probable correlation between statins and CAV1 also suggesting a potential pleiotropic value of statins beside lipid reduction [ 64 ]. In contrast another study reported that statin increased CAV1 expression, but decreased the density of caveolae while the overall raft density was unaffected.…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that small decreases in aldosterone sufficient to modify KIM-1 levels did occur, but we were unable to detect these differences. In addition, it is possible that the stimulatory effects of a chronic ANG II infusion—a continuous ANG II infusion for three days longer than the duration of ANG II infusion in the previous human and animal studies [ 43 , 57 ]—may have partially overcome the inhibitory effects of simvastatin on aldosterone in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Second, since our previous study reported a decrease in aldosterone production by zona glomerulosa cells with simvastatin in male rats [ 43 ], there could be a biological sex difference in the relationship between simvastatin and aldosterone levels. However, two publications from our group showed no interaction between statin use and aldosterone levels with sex in humans [ 43 , 57 ]. Third, simvastatin could have an effect not only on reducing aldosterone production but also on MR activity.…”
Section: Discussionmentioning
confidence: 96%
“…The lipophilic statins atorvastatin and simvastatin appear to reduce angiotensin II sensitivity and to downregulate AT1R in humans [30]. Lipophilic statins (particularly simvastatin)-but not hydrophilic statins-are associated with lower aldosterone levels [29,31]. We speculate that the aldosterone-lowering effect may be another mechanism by which statins protect against aortic dissection.…”
Section: Study Strengths and Limitationsmentioning
confidence: 87%